2022
DOI: 10.3390/pharmaceutics14030507
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of Nanolipid-Based Formulation of Diclofenac Sodium: In Vitro Characterization and Preclinical Evaluation

Abstract: In the present research study, we formulate bilosomes (BMs) of diclofenac (DC) for oral delivery for enhancement of therapeutic efficacy (anti-inflammatory disease). The BMS were prepared by thin film hydration method and optimized by Box–Behnken design (BBD) using cholesterol (A), lipid (B), surfactant (C), and bile salt (D) as formulation factors. Their effects were evaluated on vesicle size (Y1) and entrapment efficacy (Y2). The optimized DC-BMs-opt showed a vesicle size of 270.21 ± 3.76 nm, PDI of 0.265 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Further clinical investigations will show their pharmaco-dynamic effects. The in vitro release and ex vivo permeation (permeability) study showed a prolonged diclofenac release with high permeation flux [29].…”
Section: Applicationmentioning
confidence: 99%
“…Further clinical investigations will show their pharmaco-dynamic effects. The in vitro release and ex vivo permeation (permeability) study showed a prolonged diclofenac release with high permeation flux [29].…”
Section: Applicationmentioning
confidence: 99%
“…Sulpiride-loaded bilosomes (Su-BLs) were prepared using the thin film hydration process [40]. In summary, soy lecithin, cholesterol, Span 60, and Su were dissolved in a mixture of methanol and chloroform (1:1) in a round-bottomed flask.…”
Section: Manufacturing Of Sulpiride-loaded Bilosomes (Su-bls)mentioning
confidence: 99%
“…It is generally accepted that a zeta potential value of more than −30 mv indicates sufcient physical stability. Terefore, a modest zeta potential value, low polydispersity index, and small particle size indicate the new EOP formulation's physical stability [25,26].…”
Section: Zeta Potentialmentioning
confidence: 99%